Androgen deprivation results in time‐dependent hypoxia in LNCaP prostate tumours: Informed scheduling of the bioreductive drug AQ4N improves treatment response. Issue 6 (23rd November 2012) - Ming, Louise; Byrne, Niall M.; Camac, Sarah Nicole; Mitchell, Christopher A.; Ward, Claire; Waugh, David J.; McKeown, Stephanie R.; Worthington, Jenny
Abstract Androgen withdrawal induces hypoxia in androgen‐sensitive tissue; this is important as in the tumour microenvironment, hypoxia is known to drive malignant progression. Our study examined the time‐dependent effect of androgen deprivation therapy (ADT) on tumour oxygenation and investigated the role of ADT‐induced hypoxia on malignant progression in prostate tumours. LNCaP xenografted tumours were treated with anti‐androgens and tumour oxygenation measured. Dorsal skin fold (DSF) chambers were used to image tumour vasculature in vivo. Quantitative PCR (QPCR) identified differential gene expression following treatment with bicalutamide. Bicalutamide‐treated and vehicle‐only‐treated tumours were re‐established in vitro, and invasion and sensitivity to docetaxel were measured. Tumour growth delay was calculated following treatment with bicalutamide combined with the bioreductive drug AQ4N. Tumour oxygenation measurements showed a precipitate decrease following initiation of ADT. A clinically relevant dose of bicalutamide (2 mg/kg/day) decreased tumour oxygenation by 45% within 24 hr, reaching a nadir of 0.09% oxygen (0.67 ± 0.06 mmHg) by Day 7; this persisted until Day 14 when it increased up to Day 28. Using DSF chambers, LNCaP tumours treated with bicalutamide showed loss of small vessels at Days 7 and 14 with revascularisation occurring by Day 21. QPCR showed changes in gene expression consistent with the vascular changes and malignant progression. Cells from bicalutamide‐treated tumours were more malignant than vehicle‐treated controls. Combining bicalutamide with AQ4N (50 mg/kg, single dose) caused greater tumour growth delay than bicalutamide alone. Our study shows that bicalutamide‐induced hypoxia selects for cells that show malignant progression; targeting hypoxic cells may provide greater clinical benefit.